1995
DOI: 10.1111/j.1447-0756.1995.tb01029.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Superoxide Dismutase in the Human Ovary and Fallopian Tube*

Abstract: Mn-SOD and Cu, Zn-SOD have different localizations and actions in human ovaries and fallopian tubes. The superoxide radical-SOD system might play an important role in ovulation and in the luteal function of the human ovary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 19 publications
2
19
0
3
Order By: Relevance
“…However, the observed lower concentration of LPO in ovulated cows in the present study may be explained by the greater level of SOD in ovulated cows, which may act as a buffer and reduce the level of LPO. In the present study, greater SOD value in ovulated cows supports the findings of Tamate et al (1995) suggesting the role of superoxide radical and SOD as a mediator for ovulation in humans. The observed increase in SOD activity in ovulated cows may due to self-protective antioxidant mechanism against the increased peroxide production required for ovulation which is thought to be associated with inflammatory like changes (Agarwal et al, 2005).…”
Section: Lpo (Nanoeq Of Hydroperoxides/ml)supporting
confidence: 95%
“…However, the observed lower concentration of LPO in ovulated cows in the present study may be explained by the greater level of SOD in ovulated cows, which may act as a buffer and reduce the level of LPO. In the present study, greater SOD value in ovulated cows supports the findings of Tamate et al (1995) suggesting the role of superoxide radical and SOD as a mediator for ovulation in humans. The observed increase in SOD activity in ovulated cows may due to self-protective antioxidant mechanism against the increased peroxide production required for ovulation which is thought to be associated with inflammatory like changes (Agarwal et al, 2005).…”
Section: Lpo (Nanoeq Of Hydroperoxides/ml)supporting
confidence: 95%
“…Therefore control of the ROS generation in genital tract could be an important determining factor in successful fertilization and subsequent implantation. Antioxidant enzymes such as SOD [71][72][73][74][75], GPx and catalase [71] are constantly expressed in mammalian oviduct. More recent study has revealed the ROS-scavenging role of epoxide hydrolase in the oviduct [76].…”
Section: Balance Of Intra-and Extra-cellular Reducing Status In Embrymentioning
confidence: 99%
“…The impact of follicular fluid oxidative stress on oocyte maturation, fertilization and implantation of embryo have received considerable attention for therapeutic measures of ovulation induction for in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) during last few years. The study assessing the relationship of oxidative stress with oocyte quality in women who underwent ovulation induction for IVF/ICSI suggested that oxidative stress might result in poor oocyte quality [8].…”
Section: Introductionmentioning
confidence: 99%